Emissivity measurements of W/TiAlN/TiAlSiN/TiAlSiON/TiAlSiO -based multilayer spectrally selective absorbers at high temperature. (1st March 2023) - Dan, A.; Sainz-Menchón, M.; Gabirondo-López, J.; Echániz, T.; Fuente, R.; López, G.A.; Barshilia, H.C.
Highlights: Total normal emissivity of solar absorber increased from 0.06 ± 0.01 (100 °C) to 0.22 ± 0.00 (600 °C) Total hemispherical emissivity does not show a significant temperature dependence. Spectral selectivity remained unchanged after emissivity measurements. Structural and morphological stability showed potential for practical application. Abstract: Solar absorber with low infrared emissivity is an important component of the solar thermal system. The major problem of these absorbers has been the high emissivity at high temperatures causing heat loss from the system. One key solution for this issue is to study the emissive characteristics of these absorbers at high temperatures. This paper describes the infrared emissivity of W/TiAlN/TiAlSiN/TiAlSiON/TiAlSiO at elevated temperatures of 100 – 600 °C. The absorber exhibits excellent spectral selectivity with a high absorptance (α) in the solar spectrum (0.25 – 2.5 µm) and low thermal emissivity (ε) in the infrared range (2.5 – 25 µm). Directional spectral emissivity measurements performed between 10 and 80° show an emissivity decrease with the angle for wavelengths below 3.5 µm, followed by an increase in emissivity at higher wavelengths that reaches a maximum at an emission angle of 70 – 80°. The total normal emissivity shows an increase from 0.064 ± 0.016 to 0.216 ± 0.003 when the measured temperature increases from 100 to 600 °C. On the other hand, the total hemispherical emissivity does not show a significant temperature dependence. Microstructural characterizations including grazing incident X-ray diffractogram (GIXRD), scanning electron microscopy (SEM), and energy dispersive X-ray analysis (EDS) confirmed the thermal stability of the sample even after high temperature exposure up to 600 °C during emissivity measurements.